Secure policies for the distributed virtual machines in mobile cloud computing - Annane, Boubakeur (2020)
Mobile Cloud Computing (MCC) is a combination of cloud computing and mobile computing through wireless technology in order to overcome mobile devices' resource limitations. In MCC, virtualization plays a key role whereas the cloud resources are shared among many users to help them achieve an efficient performance and exploiting the maximum capacity of the cloud’s servers. However, the lack of security aspect impedes the benefits of virtualization techniques, whereby malicious users can violate and damage sensitive data in distributed Virtual Machines (VMs). Thus, this study aims to provide protection of distributed VMs and mobile user’s sensitive data in terms of security and privacy. This study proposes an approach based on cloud proxy known as Proxy-3S that combines three security policies for VMs; user’s access control, secure allocation, and secure communication. The Proxy-3S keeps the distributed VMs safe in different servers on the cloud. It enhances the grants access authorization for permitted distributed intensive applications’ tasks. Furthermore, an algorithm that enables secure communication among distributed VMs and protection of sensitive data in VMs on the cloud is proposed. A prototype is implemented on a NetworkCloudSim simulator to manage VMs security and data confidentiality automatically. Several experiments were conducted using real-world healthcare distributed application in terms of efficiency, coverage and execution time. The experiments show that the proposed approach achieved lower attacker’s efficiency and coverage ratios; equal to 0.35 and 0.41 respectively in all experimented configurations compared with existing works. In addition, the execution time of the proposed approach is satisfactory ranging from 441ms to 467ms of small and large cloud configurations. This study serves to provide integrity and confidentiality in exchanging sensitive information among multistakeholder in distributed mobile applications.